Europe's energy dependency and Russia's commercial assertiveness - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2008)
Europe is dependent on Russia for its energy supply and finds itself at odds with designing a policy that addresses its rising number of concerns over Russia while not putting its energy imports at risk. Russia's new assertiveness, in energy and as well as in other external relations, has repeatedly led it to bully its trading partners, including the EU. Foreign investors increasingly find Russia an unstable destination for investments, where commercial rule of law still widely remains an alien concept. Trade and investment policies are unclear and subject to unannounced and arbitrary amendments. With power being increasingly concentrated in the Kremlin and around the former President, Vladimir Putin, Russian politics has slithered towards authoritarianism. In this new paper, Fredrik Erixon takes stock of past and future development in Russia and discusses how Europe should design a policy which accommodates its energy supply as well as the interests of European investors in Russia.
Keywords: 330; EU-Energiepolitik; Auslandsinvestition; Autoritarismus; Russland